2011
DOI: 10.3892/mmr.2011.428
|View full text |Cite
|
Sign up to set email alerts
|

Mutations of the Connexin 26 gene in families with non-syndromic hearing loss

Abstract: Abstract. autosomal recessive non-syndromic hearing impairment (arnSHi) is caused by mutations in the gap junction gene GJB2 (connexin 26; cx26) in numerous human populations. The aim of this study was to determine the frequency of six GJB2 mutations in 50 Syrian families with congenital deafness and in 180 controls. Pcr-rFlP was used to detect the 35delG, 167delT, M34T, W24X, W77r and e47X mutations, and direct sequencing was performed for the 35delG mutation. The data revealed a high prevalence of the 35delG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 25 publications
(30 reference statements)
1
11
1
Order By: Relevance
“…The 35delG variant which is common worldwide was detected in 16.7% of Syrian families with nonsyndromic moderate to profound HI. Our results differ from a previous study by Al-Achkar et al who found 35delG mutation in 30% of Syrian families, almost double that in our study [12]. This conflict is probably due to the difference in study areas.…”
Section: Discussioncontrasting
confidence: 99%
“…The 35delG variant which is common worldwide was detected in 16.7% of Syrian families with nonsyndromic moderate to profound HI. Our results differ from a previous study by Al-Achkar et al who found 35delG mutation in 30% of Syrian families, almost double that in our study [12]. This conflict is probably due to the difference in study areas.…”
Section: Discussioncontrasting
confidence: 99%
“…According to the procedure of Al-Achkar et al (31), mutation screening was carried out using direct DNA sequence analysis. The coding sequence of the BMP15 gene was amplified by PCR using the primers described in Table 2 (15).…”
Section: Polymerase Chain Reaction and Dna Sequencingmentioning
confidence: 99%
“…According to the procedure of Al-Achkar et al (11), mutation screening was performed using direct DNA sequence analysis. The whole coding sequence of the SRY gene was amplified by polymerase chain reaction (PCR) using the primers previously described (12).…”
Section: Case Reportmentioning
confidence: 99%